The Influence of Religiousity and Income on Zakat Awareness and Interest in Paying Zakat - Nur Adilla; Yenni Samri Julianti Nasution; Sugianto Sugianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
Zakat given to mustahiq will play a role as a supporter of their economic improvement if it is consumed in productive activities. The utilization of productive zakat has a concept of careful planning and implementation, such as examining the causes of poverty, lack of working capital, and lack of employment opportunities. Therefore, zakat has a very strategic role in poverty alleviation efforts or economic development. This study is a descriptive quantitative study that examines the independent, dependent, and intervening variables related to the influence of religiousity and income on interest in paying directly and indirectly through zakat awareness of zakat. Located at LAZ Nurul Hayat Medan using as many as 100 mustahiq. The results of the research show that the variables of religiousity and income affect the interest in paying zakat directly or indirectly through zakat awareness at LAZ Nurul Hayat Medan.